Manifestasi Klinis dan Manajemen Autoimmune Anemia Hemolytic (AIHA): Laporan Kasus Pada Pasien Perempuan Usia 40 Tahun - Jodi Setiawan; Albert Tri Rustamadji (Universitas Pahlawan Tuanku Tambusai, 2025)
Autoimmune hemolytic anemia (AIHA) is decompensated acquired hemolysis caused by the body's immune system working against its own red blood cell antigens. A 40-year-old female patient came to the emergency room with complaints of black stools like tar, her eyes looked yellow, her body felt weak and she had a headache that had been felt for 5 days before she was admitted to hospital. The patient had a similar complaint which was felt approximately 4 years ago. On physical examination of the eyes, anemic conjunctiva and icteric sclera were found. On abdominal examination, grade 1-2 splenomegaly was found. Laboratory examination revealed a decrease in the number of erythrocytes, hemoglobin, hematocrit, platelets and an increase in the number of SGPT, SGOT, total bilirubin, direct bilirubin and indirect bilirubin. On examination of the peripheral blood images, mild anisocytosis, polychromasis and thrombocytopenia were found. Treatment for these patients is by using corticosteroids.